Estimating Fishing Effort and Spatio-Temporal Distribution of Longline Vessels in the Indian Ocean - Utama, Febrianto W.; Hoenner, Xavier; Hardesty, Britta Denise; Peel, David; Ford, Jessica H.; Adams, Vanessa; Wilcox, Chris (Frontiers in Marine Science, 2021)
Protein from fish is essential for feeding the world’s population and is increasingly recognized as critical for food security. To ensure that fisheries resources can be sustainably maintained, fisheries management must be appropriately implemented. When logbook and landing records data are not complete or are incorrect, it is challenging to have an accurate understanding of catch volume. Focusing on Indonesian longline vessels operating in the Indian Ocean from 2012–2019 (n = 1124 vessels), our aims were to (1) assess compliance through identification of landing sites and potentially illicit behavior inferred by interruptions in VMS transmission, and (2) understand how the fishery operates along with quantifying the spatio-temporal distribution of fishing intensity by applying a Hidden Markov Model, which automatically classified each VMS position as fishing, steaming and anchoring. We found vessel compliance gaps in 90% of vessels in the dataset. Compliance was questionable due both to the widespread occurrence of long intermissions in relaying VMS positions (mean = 17.8 h, n = 973 vessels) and the use of unauthorized landing sites. We also observed substantial changes in fishing effort locations among years. The introduction of regulatory measures during the study period banning transshipment and foreign vessels may be responsible for the spatial shift in fishing activity we observed, from encompassing nearly the whole Indian Ocean to more recent intense efforts off western Sumatra and northern Australia.